2015
DOI: 10.18632/oncotarget.5133
|View full text |Cite
|
Sign up to set email alerts
|

A novel retroviral mutagenesis screen identifies prognostic genes in RUNX1 mediated myeloid leukemogenesis

Abstract: Using a novel retroviral shuttle vector approach we identified genes that collaborate with a patient derived RUNX1 (AML1) mutant. RUNX1 mutations occurs in 40% of myelodysplastic syndromes (MDS). MDS are a group of hematopoietic stem cell disorders that are characterized by dysplasia that often progress to acute myeloid leukemia (AML). Our goal was to identify genes dysregulated by vector-mediated genotoxicity that may collaborate with the RUNX1 mutant (D171N). D171N expressing cells have a survival and engraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Their pathological relevance and underlying mechanisms are unknown. Finally, another retroviral mutagenesis screen found insertions in Itpkb to synergize with a retrovirally expressed, AML-associated Runx1- mutant in promoting murine BM progenitor outgrowth ( 171 ). The same study found that ITPKB amplifications and mRNA upregulation associate with poor survival in human AML.…”
Section: Ip 4 Dampens Store-operated Ca mentioning
confidence: 99%
“…Their pathological relevance and underlying mechanisms are unknown. Finally, another retroviral mutagenesis screen found insertions in Itpkb to synergize with a retrovirally expressed, AML-associated Runx1- mutant in promoting murine BM progenitor outgrowth ( 171 ). The same study found that ITPKB amplifications and mRNA upregulation associate with poor survival in human AML.…”
Section: Ip 4 Dampens Store-operated Ca mentioning
confidence: 99%